Evaluación de harina de follaje de yuca (Manihot esculenta) y ácido acético como suplemento en la dieta de pollos COBB 500 - Bravo Bravo, Kelvin Leonardo (2023)
This research was developed on the Dos Esthelas farm in the Pin site, Sucre canton, Manabí province; where the use of cassava foliage flour (Manihot esculenta) and acetic acid as a supplement in the diet of Cobb 500 chickens was evaluated. For this, the cassava foliage flour was characterized bromatologically, by defining five treatments : T0 Commercial Food (AC), T1 (AC) and 5% foliage meal, T2 (AC), 5% foliage meal and 1% acetic acid, T3 (AC) and 10% foliage meal and T4 (AC), 10% foliage flour and 1% acetic acid. A Completely Randomized design was used to execute the Analysis of Variance and Tukey tests at 5%, developed using the InfoStat 2022 Software. The results show that the cassava foliage flour had a humidity of 17.26%; protein 22.62%; fiber 12.01% and ash 11.25%. None of the productive parameter variables showed statistical differences between treatments. However, treatments 2 and 4 obtained a more relevant weight gain, final weight, productive index and feed conversion, while the cost-benefit was favorable for T2 and T4, which allows us to infer that they could be economically profitable.